Scaffolding Motor Skill Acquisition: The Role of Video-Based Feedback in Enhancing Volleyball Technical Competency and Cognitive Self-Regulation - Mohammad Romdani; Dyas Andry Prasetyo; Andi Fepriyanto (Assyfa Learning Journal, 2026)
Background: The transition from declarative knowledge to procedural technical proficiency in sports remains a critical challenge in physical education, often hindered by traditional feedback methods that lack cognitive scaffolding. Objective: This study aimed to examine the effectiveness of structured video analysis as an instructional media tool for improving volleyball player performance and facilitating learner self-regulation. Methods: A sequential mixed-methods approach was employed, integrating quantitative performance metrics with qualitative analysis of athlete feedback experiences to evaluate the pedagogical impact of video-based intervention. Results: The findings indicate that video-based feedback significantly enhances both technical execution and tactical decision-making by bridging the gap between perceived actions and actual movement patterns, thereby strengthening learners’ metacognitive awareness. Conclusion: Video analysis serves as a powerful instructional scaffold in modern sports learning ecosystems, promoting effective knowledge transmission and professional competency in physical education settings.